2020
DOI: 10.1039/d0qo00818d
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed selective defluorinative sulfenylation for the synthesis of fluorovinylthioethers

Abstract: An efficient transformation of trifluoromethylated compounds to monofluoroalkenes was developed through Pd-catalyzed selective defluorinative sulfenylation. A variety of α-fluorovinylthioethers were prepared in good yields from α-trifluoromethylated benzyl bromides and odorless...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Based on previous literature reports and above experimental results, , a plausible mechanism was depicted in Scheme . Initially, the RS – anion is produced from the reaction of disulfide with PPh 3 and water under basic condition .…”
Section: Resultsmentioning
confidence: 98%
“…Based on previous literature reports and above experimental results, , a plausible mechanism was depicted in Scheme . Initially, the RS – anion is produced from the reaction of disulfide with PPh 3 and water under basic condition .…”
Section: Resultsmentioning
confidence: 98%
“…On the basis of the experimental results aforementioned and the previous reports, 1,2,6–14 we proposed a mechanism (Scheme 5). Initially, Ni 0 complex is formed under reductive reaction conditions, 1,2 followed by coordination and oxidative addition to a C–F bond of trifluoropropan esters 1 to form intermediate I .…”
mentioning
confidence: 76%
“…9 Additionally, electrochemistry 10 and photochemistry 11 methodologies have been applied successfully to activate C(alkyl)–F bond through the generation of carbon radicals. In the realm of transition-metal catalysis, defluorinative functionalization involving the cleavage of C(alkyl)–F bond has been achieved by the research groups led by Xu 12 and Zhang 13 with Pd or Cu. 14 Herein, we wish to report an ester or amide group assisted nickel-catalysed reductive defluorinative sulfuration of trifluoropropionic acid derivatives with Zn as reductant (Scheme 1c).…”
mentioning
confidence: 99%
“… Such methodologies have been well-studied with the use of trifluoromethylarenes and trifluoromethylalkenes as substrates (Figure a,b, respectively). Specifically, the defluorinative conversions of trifluoromethylarenes to difluoromethylarene products include allylation, alkylation, arylation, hydrogenation, thiolation, halogenation, and phosphonium/pyridinium salt formation. , The reactions are mediated by a Lewis acid, , Lewis base, transition metal, , photocatalyst, , and reducing reagent. , Moreover, the reactions of trifluoromethylalkenes have been reported to proceed through S N 2′ and ipso -substitution mechanisms in the presence of a nucleophile, producing gem -difluoroalkenes and αα-difluoroallyl products, respectively. , Compared with these strategies, the defluorinative functionalization of (2,2,2-trifluoroethyl)­arenes is still immature (Figure c). Indeed, limited examples exist in the literature: DePuy et al reported that (2,2,2-trifluoroethyl)­arenes react with 2 equiv of KO- t -Bu to form (2-( tert -butoxy)-2-fluorovinyl)­arenes (Figure c-i), while Zhang et al demonstrated that palladium catalyzes the reactions of α-trifluoromethylated benzyl bromides with disulfides to afford α-fluorovinylthioethers (Figure c-ii) . Both reactions were described to proceed through the generation of a gem -difluorostyrene intermediate .…”
mentioning
confidence: 99%